Spectrum sensing in cognitive radio networks - Chua, Lamont Sze Hean (Nanyang Technological University, 2021)
Cognitive radio (CR) has been introduced as an innovative solution to improve spectral efficiency. Due to the regulatory arrangement, spectral bands have been licensed to different service groups and operators. Recent studies showed that the under-utilization of the allocated spectrum was quite common. In a CR network, when a licensed primary user (PU) is not using the frequency spectrum, the unlicensed secondary users (SUs) can access the same frequency band. Hence, individual SUs need to conduct spectrum sensing and determine the operating status of the PU. In this report, different spectrum sensing techniques will be discussed and more emphasis will be given to the method of energy detection in different fading environments. MATLAB software is used for the simulations.